(untitled) (Medico Legal Update, 2021)
The aim of this study is to predict the incidence of diabetic foot syndrome in type 2 diabetic patients by measuring some parameters (IL-6, FBS, MDA, CP, BMI). Samples were obtained from (75) type II diabetic patients with and without diabetic complications (diabetic foot and diabetic neuropathy), as well as (25) healthy controls as a control group. They were divided into four groups: Group A (the control group):- It included (25) healthy individuals aged between (35-70 years). Group B (Diabetics type II without complications):- Includes (25) patients, their ages range (35-70 years). Group C (diabetic patients with diabetic neuropathy):- It included (25) patients whose ages ranged from (35-70 years). Group D (diabetic patients with diabetic foot syndrome): - Included (25) patients whose ages ranged from (35-70 years). The results showed a significant increase in the levels of (IL-6, FBS, MDA, CP) in all groups of type II diabetes patients with and without complications compared to the control group (P? 0.05). There was a significant increase in the parameters measured in the group of diabetic patients with type II diabetic foot syndrome (DF) compared to the group of diabetic patients with type II disease Diabetic neuropathy (DN), and the results also showed a significant increase in group DN compared to group of type II diabetic patients (DM) (P? 0.05). Our study show Interleukin-6 values, as well as oxidative stress, could predict the future incidence of diabetic foot syndrome.